Participation of Civil Society Institutions in Civil Service Competitions - Магновський, Ігор Йосифович; Магновський, І. Й.; Магновский, Игорь Иосифович; Mahnovskyi, Ihor Y.; Стець, Олег Миколайович; Стець, О. М.; Стец, Олег Николаевич; Stets, Oleh M.; Негара, Родіон Віталійович; Негара, Р. В.; Негара, Родион Витальевич; Nehara, Rodion V. (Hampstead Psychological Associates, 2020)
Currently, in Ukraine, attempts of civil society institutions to participate in public problem solving seem to be unsuccessful, including in competitions for vacant civil service posts. Reevaluation of their functional role in the competition is considered to be one of the main tasks of development of democratic governance. The purpose of this article is to determine possible ways to improve efficiency of interaction between Ukrainian civil society institutions and public administration subjects in competitions for vacant civil service posts; to define a single concept of governance humanization and democratization and to offer specific recommendations on reforming citizen participation in competitions for vacant civil service posts in Ukraine. During the research, general and special methods of scientific knowledge were used: system analysis method, dialectical method, formal logical method, and structural functional method, as well as certain empirical methods. The authors came to the conclusion on poor interaction between public administration subjects and civil society institutions in competitions for vacant civil service posts in Ukraine. The positive effect of new forms of public involvement can be improved by promotion of e-participation of citizens in the public administration. Free access to electronic reflection of any public administration subject’s activity is believed to simplify public involvement in making decisions. The results of the research seem to be interesting and useful for national legislators and public administration subjects against actualized tendencies in democratization and humanization of administrative processes. The research subject is considered in Ukraine for the first time and seems to have the prospect of further development.

В даний час в Україні спроби інститутів громадянського суспільства взяти участь у вирішенні державних проблем виявляються безуспішними, зокрема в конкурсах на вакантні посади державної служби. Переоцінка їх функціональної ролі у конкуренції вважається одним із головних завдань розвитку демократичного управління. Мета цієї статті - визначити можливі шляхи підвищення ефективності взаємодії між українськими інститутами громадянського суспільства та суб’єктами державного управління в конкурсах на вакантні посади державної служби; визначити єдину концепцію гуманізації та демократизації управління та запропонувати конкретні рекомендації щодо реформування участі громадян у конкурсах на вакантні посади державної служби в Україні. Під час дослідження використовувались загальні та спеціальні методи наукового пізнання: метод системного аналізу, діалектичний метод, формально-логічний метод та структурний функціональний метод, а також певні емпіричні методи. Автори дійшли висновку про погану взаємодію між суб'єктами державного управління та інститутами громадянського суспільства в конкурсах на вакантні посади державної служби в Україні. Позитивний ефект від нових форм залучення громадськості може бути покращений шляхом сприяння е-участі громадян у державному управлінні. Вважається, що вільний доступ до електронного відображення діяльності будь-якого суб’єкта державного управління спрощує участь громадськості у прийнятті рішень. Результати дослідження видаються цікавими та корисними для вітчизняних законодавців та суб'єктів державного управління проти актуалізованих тенденцій демократизації та гуманізації адміністративних процесів. Тема дослідження розглядається в Україні вперше і, вбачається, має перспективу подальшого розвитку.

В настоящее время в Украине попытки институтов гражданского общества принять участие в решении государственных проблем оказываются безуспешными, в частности в конкурсах на вакантные должности государственной службы. Переоценка их функциональной роли в конкуренции считается одной из главных задач развития демократического управления. Цель этой статьи - определить возможные пути повышения эффективности взаимодействия между украинскими институтами гражданского общества и субъектами государственного управления в конкурсах на вакантные должности государственной службы; определить единую концепцию гуманизации и демократизации управления и предложить конкретные рекомендации по реформированию участия граждан в конкурсах на вакантные должности государственной службы в Украине. В ходе исследования использовались общие и специальные методы научного познания: метод системного анализа, диалектический метод, формально-логический метод и структурный функциональный метод, а также определенные эмпирические методы. Авторы пришли к выводу о плохом взаимодействии между субъектами государственного управления и институтами гражданского общества в конкурсах на вакантные должности государственной службы в Украине. Положительный эффект от новых форм привлечения общественности может быть улучшен путем содействия е-участия граждан в государственном управлении. Считается, что свободный доступ к электронному отражению деятельности любого субъекта государственного управления упрощает участие общественности в принятии решений. Результаты исследования представляются интересными и полезными для отечественных законодателей и субъектов государственного управления против актуализированных тенденций демократизации и гуманизации административных процессов. Тема исследования рассматривается в Украине впервые и, предполагается, имеет перспективу дальнейшего развития.
Mahnovskyi I. Y. Participation of Civil Society Institutions in Civil Service Competitions / I. Y. Mahnovskyi, O. M. Stets, R. V. Nehara // International Journal of Psychosocial Rehabilitation. – V. 24 (8). - Hampstead Psychological Associates, 2020. – P. 9423-9431.
Keywords: civil service; competition; competition commission; public associations; державна служба; конкурс; конкурсна комісія; громадські об’єднання; государственная служба; конкурс; конкурсная комиссия; общественные объединения; Research Subject Categories::LAW/JURISPRUDENCE